Therapeutic effect of sunitinib malate and its influence on blood glucose concentrations in a patient with metastatic insulinoma. Issue 6 (June 2013) - Chen, Jianpeng; Wang, Caixia; Han, Junqing; Luan, Yi; Cui, Yangang; Shen, Rong; Sha, Dan; Cong, Lei; Zhang, Zheng; Wang, Weibo
Standard cytotoxic chemotherapy has limited efficacy in advanced insulinomas, and control of blood glucose concentrations in these patients may be difficult. This article describes an elderly (74-year-old) man with metastatic insulinoma and severe hypoglycemia who was treated with repeated 6-week cycles of oral sunitinib malate (25 mg/day for 4 weeks, followed by 2 weeks off treatment). After treatment for more than 2 years, his condition improved and he continued to have a good quality of life with no evidence of tumor progression based on PET/CT findings. Although sunitinib treatment lowered the patient's blood glucose concentrations further and induced repeated symptomatic hypoglycemic episodes, he was able to tolerate the treatment well after changing the timing of sunitinib dosing and adjusting his diet.